How to get an efficient swim technique in triathlon? - Cala Mejias, A.; Cejuela, R. (Journal of Human Sport & Exercise, 2011)
Both in swimming and triathlon, depending on the event, the athletes have to swim the same distance (1500 meters) but the goal is different. In swimming, the goal is to be the fastest (winning the race). In triathlon, the goal is to make the first group saving as much energy as possible. Thus, the main objective of this manuscript is to find out how coaches can make the athletes to achieve an efficient swim technique that requires less amount of energy during a triathlon competition. The triathletes need to develop a more efficient and economic swim technique by reducing the speed fluctuations within the swim stroke. Basing on the "kayak principle", there are some strategies they can be adopted during the training sessions to achieve a continue propulsion through the stroke. The use of different drills based on the "feeling of the stroke rhythm" as well as the available equipment, can help to achieve technique that requires less amount of energy to swim at the same pace. However, there are also some considerations to take into account during a normal training session, as other sets, aids or equipment can affect the coordination between arms as well.